Observer-based robust H∞ control for fuzzy systems using two-step procedure. - Ji-Chang Lo (IEEE Transactions on fuzzy systems)
This paper investigates both robust H∞ analysis and synthesis problems involving observer-based fuzzy control via linear matrix inequality methods for which efficient optimization techniques are available. The observer and controller are capable of disturbance-rejection in the presence of unknown but bounded disturbance. We present results in a unified fashion applicable to both continuous- and discrete-time problems with or without uncertainty. Finally, the validity and applicability of the approach are demonstrated by examples.